Morphological and phenological properties of sour cherry varieties grown in Hungary and their inter-incompatibility relations - Nyéki, J.; Szabó, Z.; Szabó, T.; Soltész, M. (International Journal of Horticultural Science, 2000)
Regular observations and experiments were performed during a 14 year period on 6 sour cherry varieties. The morphological traits of leaves and fruits were compared, and the phenology of blooming as well as of ripening dates served to start an estimation of the possibilities of mutual pollination and the planning of harvest operations. Experiments involved obligate autogamy, artificially controlled allogamy and open pollination in order to reveal self-fertility, self-sterility or inter-incompatibility relations. The varietal characters represent, each, different values in the distinction of the items, because of their intra-varietal variability. From that point of view, the most reliable are the data of blooming and ripening time, fruit size and the fertility relations. Inter-incompatibility was observed between the group of self-fertile, "Pándy type" varieties (`Újfehértói fürtös’, ‘Debreceni bőtermő’, ‘Kántorjánosi’) on one side and the selection of Pándy 7’, a self-sterile variety on the other side. Unilateral incompatibility has been detected within the former group of new, self-fertile varieties, the combinations: (`Újfehértói fürtös’ x ‘Debreceni bőtermő’ as well as `Újfehértói fürtös’ x Kántorjánosi’. Our results prove the close kinship between those three new varieties and the original Pándy variety on the base of being highly similar in their morphology and also of the fact of their inter-incompatibility, though unilateral.